Early detection and curative treatment of hepatocellular carcinoma: A cost‐effectiveness analysis in France and in the United States - Cadier, Benjamin; Bulsei, Julie; Nahon, Pierre; Seror, Olivier; Laurent, Alexis; Rosa, Isabelle; Layese, Richard; Costentin, Charlotte; Cagnot, Carole; Durand‐Zaleski, Isabelle; Chevreul, Karine (Hepatology (Baltimore, Md.), 2017)
Hepatocellular carcinoma (HCC) is the leading cause of death in patients with cirrhosis. Patients outside clinical trials seldom benefit from evidence‐based monitoring. The objective of this study was to estimate the cost‐effectiveness of complying with HCC screening guidelines. The economic evaluation compared surveillance of patients with cirrhosis as recommended by the guidelines (“gold‐standard monitoring”) to “real‐life monitoring” from the health care system perspective. A Markov model described the history of the disease and treatment course including current first‐line curative treatment: liver resection, radiofrequency ablation (RFA), and liver transplantation. Transition probabilities were derived mainly from two French cohorts, CIRVIR and CHANGH. Costs were computed using French and U.S. tariffs. Effectiveness was measured in life years gained (LYG). An incremental cost‐effectiveness ratio (ICER) was calculated for a 10‐year horizon and tested with one‐way and probabilistic sensitivity analyses. The cost difference between the two groups was $648 ($87,476 in the gold‐standard monitoring group vs. $86,829 in the real‐life monitoring group) in France and $11,965 ($93,795 vs. $81,829) in the United States. Survival increased by 0.37 years (7.18 vs. 6.81 years). The ICER was $1,754 per LYG in France and $32,415 per LYG in the United States. The health gain resulted from earlier diagnosis and access to first‐line curative treatments, among which RFA provided the best value for money. Conclusion: Our results indicate that gold‐standard monitoring for patients with cirrhosis is cost‐effective, attributed to a higher probability of benefiting from a curative treatment and so a higher survival probability. (Hepatology 2017;65:1237‐1248)